2009
DOI: 10.1016/j.engfracmech.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stable crack extension in aluminium sheet material using the crack tip opening angle determined optically and by the δ5 clip gauge technique

Abstract: Tests standards aimed at deriving fracture toughness data and crack resistance curves under low constraint condition have recently been finished by ASTM and are in the final stage within ISO. These standards cover various experimental methods for determining critical crack tip opening angles, CTOA, for characterising stable crack extension in sheet material. In this paper, some key items of these standard methods are validated, namely the experimental determination of the crack tip opening angle by optical obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The critical d 5 value and the d 5 -R curve are utilized as alternatives to describe the resistance of ductile sheet materials to stable crack extension under low-constraint conditions. More detailed discussions on this topic were given recently by Heerens and Schodel [223].…”
Section: Ctoa Testing and Astm E2472 Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical d 5 value and the d 5 -R curve are utilized as alternatives to describe the resistance of ductile sheet materials to stable crack extension under low-constraint conditions. More detailed discussions on this topic were given recently by Heerens and Schodel [223].…”
Section: Ctoa Testing and Astm E2472 Developmentmentioning
confidence: 99%
“…This newer standard uses C(T) and M(T) specimens made from thin-sheet materials in order to achieve low constraint conditions at the crack tip. The standard was validated by Heerens and Schodel [223] using a comprehensive data set on the stable crack extension in an aluminum sheet material with a thickness of 3 mm. The CTOA fracture criterion now becomes one of the most promising fracture criterion used for characterizing the stable tearing in thin metallic materials 224.…”
Section: Ctoa Testing and Astm E2472 Developmentmentioning
confidence: 99%
“…In the past, various mechanisms were studied and proposed to estimate CTOA for stable crack growth [1][2][3][4][5][6][7]. Especially for fully plastic crack growth in low strength materials, the sliding-off and shear-cracking model suggested by McClintock et al [1], among others, was found to best serve to estimate CTOA.…”
Section: Introductionmentioning
confidence: 98%
“…In previous projects, a slot design in the loading arms was successfully used [43]. An example specimen for static tensile load test is shown in Figure 4.…”
Section: Specimen Designmentioning
confidence: 99%
“…Photo of a HZG test sample for static tensile loading test with load-diffusion slots [43] For the purpose of this study, i.e. testing under cyclic loads, the basic geometry shown in Figure Specimen design was based on FEA [31].…”
Section: Figurementioning
confidence: 99%